Association of the Weight-Adjusted-Waist Index With Risk of All-Cause Mortality: A 10-Year Follow-Up Study - Cai, Shuang; Zhou, Lin; Zhang, Yue; Cheng, Bokai; Zhang, Anhang; Sun, Jin; Li, Man; Su, Yongkang; Bao, Qiligeer; Zhang, Yan; Ma, Shouyuan; Zhu, Ping; et al. (Frontiers in Nutrition, 2022)
Abstract Background: To explore the association between weight-adjusted-waist index (WWI) and the risk of all-cause mortality in one urban community-dwelling population in China. Methods: This is a prospective cohort study with a sample of 1863 older adults aged 60 years or over in Beijing who completed baseline examinations in 2009-2010 and a 10-year follow-up in 2020. WWI was calculated as waist circumference (cm) divided by the square root of weight (kg). Cox regression analysis was performed to investigate the significance of the association of WWI with all-cause mortality. The area under the receiver operating characteristic (ROC) curves were used to compare the ability of each obesity indexes to predict mortality. Results: During a median follow-up of 10.8 years (ranging from 1.0 to 11.3 years), 339 deaths occurred. After adjustment for potential confounders, the hazard ratios (HRs) for all-cause mortality progressively increased across tertile of WWI. Compared with the lowest WWI category (tertile1<10.68cm/√kg), with WWI 10.68 to 10.24cm/√kg, and≥11.25cm/√kg, the HRs (95% confidence intervals (CIs)) for all-cause mortality were 1.58(1.12-2.22), and 2.66(1.80-3.92), respectively. In stratified analyses, the association between WWI and the risk of all-cause mortality persisted. The area under ROC for WWI was higher for all-cause mortality than BMI, WHtR, and WC. Conclusion: WWI was associated with a higher risk for all-cause mortality, and the associations were more robust with the highest WWI category.